Is Malondialdehyde (MDA) used as a Oxidative Stress Marker in Chronic Obstructive Pulmonary Disease (COPD) & Cigarette Smokers - Pramod Ingale; Pooja Rai; Vaishnavi Salunkhe; NT Awad (Dr. Annil Mahajan, 2022)
Background: The present study was aimed to study alterations in levels of oxidants and antioxidants in Chronic Obstructive Pulmonary disease (COPD) patients. Methods: 100 patients of diagnosed COPD & 100 cigarette smokers in age group of 40 to 65 years were included in the study and results were compared with controls. Glutathione peroxidase (GPX), glutathione reductase (GR), superoxide dismutase (SOD), Vitamin C as an antioxidants & Malondialdehyde (MDA) as an oxidant were estimated. Results: Significant (<0.05) decreased levels of Glutathione peroxidase (GPX), glutathione reductase (GR), superoxide dismutase (SOD), Vitamin C were found in COPD and chronic smokers as compared to controls. MDA was significantly (<0.05) increased as compared to controls. Conclusion: COPD & Cigarette smokers generate increased amounts of Reactive oxygen species (ROS). ROS produce many of the pathophysiologic changes associated with COPD and may contribute further to its pathogenesis. The primary defence against Reactive oxygen species (ROS) is endogenous antioxidants, which are found to be altered in COPD & smokers. Antioxidants inhibit the changes produced by ROS & they get confused in the process. So, antioxidants can be used as a marker for prevention of COPD due to Reactive oxygen species.